New Perspectives on Turkey roundtable on Ayşe Buğra's book: Social Policy in Capitalist History: Perspectives on Poverty, Work and Society (Edward Elgar Publishing 2024) - Bugra, Ayse; Standing, Guy; Fischer, Andrew; Agartan, Tuba; Akkan, Basak; Turem, Z. Umut (Cambridge Univ Press, 2025)
We are happy to publish a roundtable debate based on the discussions carried out at the webinar organized by our journal to discuss Ay & scedil;e Bu & gbreve;ra's latest book, Social Policy in Capitalist History: Perspectives on Poverty, Work and Society. Bu & gbreve;ra's important contribution to the field of social policy is critically evaluated by Guy Standing, Andrew Fischer, and Tuba A & gbreve;artan. Social policy is an important field for New Perspectives on Turkey, one in which we try to publish research articles, book reviews, and commentaries. We are hoping that this roundtable debate, by revisiting the theoretical and historical foundations of social policy via Standing's, Fischer's, and A & gbreve;artan's takes on Bu & gbreve;ra's arguments, will contribute to the enhancement of the ongoing critical discussions at a time during which the capitalist economy is going through a major transformation at the end of the first quarter of the twenty-first century. We are grateful to Ba & scedil;ak Akkan for organizing and moderating the webinar and seeing through the publication process and our associate editor Z. Umut T & uuml;rem for making it possible.
Keywords: [Keyword Not Available]